APLIKASI ERGONOMI PADA SERAGAM OLAHRAGA DAPAT MENINGKATKAN KENYAMANAN DAN MEMPERBAIKI RESPON SUHU KULIT KETIKA BEROLAHRAGA PADA SISWA SMP DI SMP “KESUMA SARI” DENPASAR BALI - Ismiyasa, Suci Wahyu; Adiputra, I Nyoman; Tirtayasa, Ketut; Purnawati, Susy (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2017)
The choice of sports uniforms should be tailored to the sports activities undertaken. For that reason, the selection of uniforms should be comfortable to use, absorb sweat, and have a circulation between clothing and skin, fit uniform size and at affordable price. The study was conducted to examine the measured application of ergonomic applications on sports uniforms that can make comfort in exercising found on junior high school students. The design of the study used pretest-posttest control group design involving 2 groups of subjects namely the Control Group and the Treatment Group of respectively 12 samples. The research was conducted at Kesuma Sari Junior High School, Sesetan, Denpasar, Bali. The measured data were age, height, body weight, ambient temperature, dress comfort questionnaire, skin temperature response and pulse recovery response. The findings of descriptive analysis showed significant differences (p <0.05) on the variables of comfort and surface temperature of the skin, no significant difference (p> 0.05) on the variable of pulse recovery. The mean value of the difference of comfort before and after exercising in the Control Group decreased by (-4.17 ± 4.668) and in the Treatment Group increased by (2.50 ± 3.477). The mean value of the skin temperature difference before and after exercising in the Control Group increased the temperature by (0.57 ° C ± 0.64) and in the Treatment Group there was a temperature increase of (0.01 ° C ± 0.65). The Mean decrease in the pulse recovery in the Control (107.03 ± 15.18) and the Treatment Groups (106.93 ± 16.37) was not much different so there is no influence between the two. It can be concluded that the ergonomic application of sport uniforms increased the comfort of exercise in the junior high school students of Kesuma sari, the ergonomics application of sport uniform may improve the skin temperature response in exercise on the junior high school students of Kesuma Sari, and the ergonomic application of sport uniform had no effect on the pulse recovery response in exercising on the students SMP Kesuma Sari.